2017
DOI: 10.1364/ao.56.000644
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pure optical nonlinearity in carbon disulfide with a high-repetition-rate femtosecond laser

Abstract: Using the close-aperture Z-scan technique, the pure nonlinear refractive index (n2) of carbon disulfide is measured with a 76 MHz repetition rate femtosecond laser. Strong interference of thermal effects exists with high-repetition-rate lasers that result in negative values of n2. We remove the thermal effect completely by continuously increasing the sample flow rate (F) in a sample cell as indicated by the change in sign of n2 from negative to positive. The positive value of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…This contrast was absent in our previous results with high repetition rate pulses and a fixed (nonscanning) beam, likely because of the temperature sensitivity of the vibrational cooling (VC) processes , in addition to the tendency of the methionine ligand to dissociate upon heating . The fact that rapid scanning restores redox contrast is also consistent with experiments showing that flowing a liquid sample rapidly through the focal spot can minimize heating effects and bring high-repetition-rate measurements of nonlinear refractive index in line with low-repetition-rate findings …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This contrast was absent in our previous results with high repetition rate pulses and a fixed (nonscanning) beam, likely because of the temperature sensitivity of the vibrational cooling (VC) processes , in addition to the tendency of the methionine ligand to dissociate upon heating . The fact that rapid scanning restores redox contrast is also consistent with experiments showing that flowing a liquid sample rapidly through the focal spot can minimize heating effects and bring high-repetition-rate measurements of nonlinear refractive index in line with low-repetition-rate findings …”
Section: Resultssupporting
confidence: 86%
“…19 The fact that rapid scanning restores redox contrast is also consistent with experiments showing that flowing a liquid sample rapidly through the focal spot can minimize heating effects and bring high-repetition-rate measurements of nonlinear refractive index in line with lowrepetition-rate findings. 20 From the λ pu = 530 nm and λ pr = 490 nm signals in Figure 1, the most prominent difference between redox states is within the subpicosecond region. Cyt-c−Fe 2+ has a narrower peak and roughly 3× the amplitude compared with Cyt-c−Fe 3+ .…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…This study indicates that the nonlinear index of refraction is prone to the pulse-to-pulse separation as compared to the nonlinear absorption, which does not show any significant change with respect to the repetition rate of the laser. This result also exhibits that working with laser pulses as low as 100 Hz or lower (Singhal, Dinda & Goswami, 2017) can give rise to almost pure nonlinear optical properties. Experimentally calculated thermal decay time from this study was found to be in good agreement with…”
Section: Discussionmentioning
confidence: 56%
“…This study indicates that the nonlinear index of refraction is prone to the pulse-to-pulse separation as compared to the nonlinear absorption, which does not show any significant change with respect to the repetition rate of the laser. This result also exhibits that working with laser pulses as low as 100 Hz or lower [46] can give rise to almost pure nonlinear optical properties. Experimentally calculated thermal decay time from this study was found to be in good agreement with the theoretically calculated thermal conduction time for both the organic liquids under consideration.…”
Section: Discussionmentioning
confidence: 58%